Financial modeling, actuarial valuation and solvency in insurance - Wuthrich, Mario V.; Merz, Michael (Berlin : Springer-Verlag, 2013)
Risk management for financial institutions is one of the key topics the financial industry has to deal with. The present volume is a mathematically rigorous text on solvency modeling. Currently, there are many new developments in this area in the financial and insurance industry (Basel III and Solvency II), but none of these developments provides a fully consistent and comprehensive framework for the analysis of solvency questions. Merz and Wüthrich combine ideas from financial mathematics (no-arbitrage theory, equivalent martingale measure), actuarial sciences (insurance claims modeling, cash)
1. Introduction Part I: Financial Valuation Principles. 2.State Price Deflators and Stochastic Discounting 3. Spot Rate Models 4. Stochastic Forward Rate and Yield Curve Modeling 5. Pricing of Financial Assets. Part II: Actuarial Valuation and Solvency. 6. Actuarial and Financial Modeling 7. Valuation Portfolio 8. Protected Valuation Portfolio 9. Solvency 10.Selected Topics and Examples. Part III: Appendix. 11. Auxiliary Considerations. with References and Index.
Includes bibliographical references and index.
Keywords: Insurance -- Mathematical models; Insurance -- Statistical methods; BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management